Penerapan Digitalisasi Bisnis untuk UMKM Kedai Kopi - Wahyudi, Triyono Arief; Iskandar, Donant Alananto; Tun Ganyang, Machmed; Ritonga, Wier (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
The coffee shop micro, small, and medium enterprises (MSMEs) are receiving considerable attention from the government due to their swift development over the last decade. The growth of coffee shop businesses is reflected in the rising number of locations, increased customer demand, and higher coffee production in Indonesia. A significant challenge for coffee shop MSMEs is their limited understanding of business digitization, which hampers their ability to seize opportunities in the coffee beverage sector. This initiative is designed to improve MSMEs' knowledge of business digitization in coffee shops. The program took place on October 28, 2022. The training methods incorporated lectures, interactive question-and-answer sessions, case studies, and role-playing exercises focused on e-promotion tools such as e-reviews, e-commerce, online communication platforms, e-catalogs, and social media. A total of 20 MSMEs participated in this event. The findings show a boost in understanding among coffee shop MSMEs regarding business digitization following the training session.